2000
DOI: 10.1097/00004836-200009000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Five-day Triple Therapy in Helicobacter pylori-positive Duodenal Ulcer

Abstract: The aim of this study was to compare the efficacy of two different 5-day proton pump inhibitor (PPI)-based triple therapies for Helicobacter pylori (Hp)-positive duodenal ulcers (DUs). Eighty-four patients received pantoprazole (Pan) 80 mg O.D. (once daily) for 1 week; 88 patients received omeprazole (Ome) 40 mg O.D. for 1 week. Patients of both groups received clarithromycin (Cla) 500 mg B.I.D. (twice daily) and amoxicillin (Amo) 1 g B.I.D. for 5 days. All of them were clinically and endoscopically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In our previous H. pylori eradication trials, we have demonstrated that double doses of PPIs were effective in inducing H. pylori -positive duodenal ulcer, while rabeprazole has shown to be efficacious in single dose (20 mg daily) as well as in double dose (40 mg daily), achieving an eradication and a healing rate as satisfactory as that of double-dose rabeprazole (40 mg) and omeprazole (40 mg daily) [10, 11, 12]. Several randomised controlled trials have compared short versus longer treatments [5, 29, 30, 31], but among these, only two studies comparing 2/4 days with 7/10 days have shown a significant difference [32, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous H. pylori eradication trials, we have demonstrated that double doses of PPIs were effective in inducing H. pylori -positive duodenal ulcer, while rabeprazole has shown to be efficacious in single dose (20 mg daily) as well as in double dose (40 mg daily), achieving an eradication and a healing rate as satisfactory as that of double-dose rabeprazole (40 mg) and omeprazole (40 mg daily) [10, 11, 12]. Several randomised controlled trials have compared short versus longer treatments [5, 29, 30, 31], but among these, only two studies comparing 2/4 days with 7/10 days have shown a significant difference [32, 33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Various triple-therapy regimens, consisting in the association of a proton pump inhibitor (PPI) with two antimicrobials (clarithromycin, amoxicillin or metronidazole), have been reported to be effective and a high eradication rate of these different drug combinations have been confirmed in Western countries [5, 6, 7]. More recently, higher doses of PPI, such as lansoprazole- or pantoprazole-based triple therapy, have been shown to be more effective than low doses of PPI in many reports [4, 7, 8, 9, 10, 11, 12]. Rabeprazole, the new member of the class of substituted benzimidazole molecules, is a potent antisecretory agent, suppressing both basal and stimulated gastric acid secretion in a dose-dependent manner [13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…[87] The major result of the aforementioned metaanalysis comparing pantoprazole with other PPIs (such as omeprazole or lansoprazole) as eradication therapy against H. pylori is that the results are the same regardless of the PPI used. [78] Thus, as graphically presented in figure 2 derived from the seven studies [88][89][90][91][92][93][94] included in the meta-analysis in which 534 patients received pantoprazole and 603 patients received other PPIs, the mean H. pylori eradication rate was 83% and 81%, respectively. The OR for this comparison was exactly 1 (95% CI, 0.61-1.64).…”
Section: Pantoprazolementioning
confidence: 99%
“…Intention-to-treat analysis. [88][89][90][91][92][93][94] OR ¼ odds ratio; 95% CI ¼ 95% confidence interval.…”
Section: Rabeprazolementioning
confidence: 99%
“…Randomized clinical trials comparing pantoprazole and omeprazole are summarized in figure 2, where it can be observed that the efficacy of both PPIs are equivalent [8,[11][12][13][14].…”
Section: Pantoprazolementioning
confidence: 99%